Predicting treatment response in psoriasis using serum levels of adalimumab and etanercept: a single‐centre, cohort study. (13th August 2013) - Mahil, S.K.; Arkir, Z.; Richards, G.; Lewis, C.M.; Barker, J.N.; Smith, C.H.
Abstract : What's already known about this topic? Tumour necrosis factor antagonist failure may be attributable to low serum drug levels, resulting from a number of factors including antidrug antibodies. Drug and antidrug antibody enzyme‐linked immunosorbent assays are commercially available but their utility in clinical practice is uncertain. Measuring serum drug and antidrug antibody levels has been proposed as a personalized approach to therapy. What does this study add? This is a pragmatic study investigating the association between serum adalimumab and etanercept levels, and clinical response in psoriasis. Adalimumab drug levels at 4 weeks predict responder status at 6 months, with low or absent levels associated with failure to achieve 50% improvement in Psoriasis Area and Severity Index. Antiadalimumab antibodies are associated with nonresponse. Summary: Background: A substantial proportion of patients with psoriasis do not respond, or lose initial response to tumour necrosis factor‐α antagonists. One possible mechanism relates to subtherapeutic drug levels due to an immunogenic antibody response. Objectives: To investigate the association between serum adalimumab and etanercept levels, antidrug antibody levels and clinical response in a cohort of patients with psoriasis using a commercially available enzyme‐linked immunoassay. Methods: In a single‐centre cohort of 56 adults with chronic plaque psoriasis initiated on adalimumab or etanercept monotherapy between 2009 and 2011, drug and antidrug antibody levels were measured at the patients' routine clinic reviews (4, 12 and 24 weeks of treatment and the last available observation). Patients' responses at 6 months were stratified into responders [75% reduction in Psoriasis Area and Severity Index from baseline (PASI 75) or Physician's Global Assessment score of 'clear' or 'nearly clear'] and nonresponders (failure to achieve PASI 50). Results: After 4 weeks, adalimumab levels were significantly higher in responders compared with nonresponders ( P = 0·003) and these higher levels were sustained at 12 and 24 weeks. Anti adalimumab antibodies were detected in 25% of nonresponders (two of eight patients, average 22·5 weeks' follow‐up) and none of the responders ( n = 23, average 26·1 weeks' follow‐up). There was no significant association between etanercept levels and clinical response at 4 weeks ( P = 0·317) and no antietanercept antibodies were detected. Lack of serum trough levels may have resulted in underestimation of the prevalence of antidrug antibodies. Conclusions: Early adalimumab drug level monitoring at 4 weeks may be useful in predicting treatment response and potentially reduce drug exposure (and associated cost) with earlier review of treatment in those with low levels. No conclusions about the value of etanercept drug monitoring can be made due to the paucity of data. Larger studies are now required to assess the clinical utility and cost‐effectiveness of these assays in personalizing therapy in psoriasis.